The Macrozoobenthos Community Structure on Artificial Reef at Penyusuk Marine, Bangka Regency - Aldia, Dia; Supratman, Okto; Muftiadi, M. Rizza (Yayasan Serumpun Karang Konservasi, 2024)
Makrozoobenthos are all types of sedentary organisms or move freely whose habitat’s in the bottom substrate of waters with a body size of more than equal to 0.5 mm. Benthos have a very important role in waters where macrozoobenthos communities must remain balanced so that aquatic ecosystems are balanced. This study aims to determine the type of macrozoobenthos, the abundance of macrozoobenthos and the structure of macrozoobenthos communities on artificial reefs in Penyusuk Marine, Bangka Regency which was sunk by PT. Arta Cipta Langgeng. Data collection will be carried out in May 2023 at an artificial reef in Penyusuk Marine, Bangka Regency. The determination of the research location point was carried out by purposive sampling and macrozoobenthos data collection using road sampling techniques and free hand picking methods. Measurement of environmental parameters was carried out in situ and ex situ as well as data analysis using Principal Component Analysis (PCA). The results of the study found 32 types of macrozoobenthos with a total of 2,745 individuals found at the three observation stations. The abundance obtained ranged from 46,04 ind/m2 – 49,01 ind/m2. The diversity value ranges from 0,60 – 0,87 so that was categorized as low, the uniformity value ranges from 0,19 – 0,27 as low was categorized and the dominance value ranges from 0,72 – 0,82 was high categorized.